2022
DOI: 10.3390/horticulturae8060521
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Examination of Phytonutrients and Antioxidant Activity of Commonly Consumed Nuts and Seeds Grown in Vietnam

Abstract: The aim of the present study was to determine the phenolics, carotenoids, B-vitamins, and antioxidant activity of nuts and seeds grown in Vietnam. The concentrations of carotenoids and B-vitamins may vary among the nuts and seeds. Watermelon seed contained the highest level of lutein while pumpkin seed was the β-carotene richest sample. Sachi inchi and sunflower seed comprised considerable levels of vitamin B1, B6, and B9. The phenolic analysis revealed that cashew contained the highest total amount of flavono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…These results were consistent with previous studies, which showed phenolic and flavonoid compounds were mainly responsible for the scavenging effects against free radicals. 9,10…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results were consistent with previous studies, which showed phenolic and flavonoid compounds were mainly responsible for the scavenging effects against free radicals. 9,10…”
Section: Resultsmentioning
confidence: 99%
“…These results were consistent with previous studies, which showed phenolic and flavonoid compounds were mainly responsible for the scavenging effects against free radicals. 9,10 For metal ion reduction, ferric and cupric ions were tested, which compared the ability of extracts to donate electrons at different pHs. The results showed that ethyl acetate, butanol, and ethanol extracts effectively reduced cupric and ferric solutions, and the reducing powers of these extracts are in line with their concentration.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…The TPC was determined using the published method. 20 Briefly, 0.1 mL of samples or standard (gallic acid solution from 0 -100 µg/mL) was mixed with 0.5 mL of 10-fold diluted, 0.4 mL of 10% Na2CO3 solutions, and 1.5 mL of deionized water. The mixture was incubated for 2h and measured spectrophotometrically at 760 nm.…”
Section: Total Phenolic Content (Tpc)mentioning
confidence: 99%
“…The scavenging activity of EOs against free radicals was determined using a DPPH (2,2-diphenyl-1-picrylhydrazyl) assay and vitamin C as a positive control. 20 The samples with concentrations ranging from 0 -100 mg/mL or standards (0.1 mL) were mixed with 0.1 mL of 0.3 mM DPPH solution. The mixtures were incubated in dark for 30 min and measured absorbance at 517 nm.…”
Section: Dpph Scavenging Assaymentioning
confidence: 99%
See 1 more Smart Citation